Impact of a global biodiversity education campaign on zoo and aquarium visitors. Issue 5 (15th May 2017) - Moss, Andrew; Jensen, Eric; Gusset, Markus
Abstract : Campaigns by zoos, aquariums, and other civil society organizations are an important tool for promoting social changes that benefit the environment. Here, we evaluate a global biodiversity education campaign's impact through a repeated‐measures survey of nearly 5000 visitors to 20 zoos and aquariums located in 14 countries. By comparing visitors' pre‐ and post‐visit responses combined across respondents, we found significant aggregate improvements in their biodiversity understanding and their knowledge of actions to help protect biodiversity. Respondents who reported seeing the education campaign's interpretive graphic panels and informative films showed a significantly higher aggregate increase in their understanding of biodiversity and actions to protect it as compared to respondents who did not see the campaign materials. These findings reaffirm the value of education at zoos and aquariums to engage members of the public with biodiversity‐related issues. The results also demonstrate that the aggregate impact from such experiences can be enhanced through coordinated public engagement initiatives.